Penyesuaian Teori Akuntansi Syari`ah: Perspektif Akuntansi Sosial dan Pertanggungjawaban - Muhamad Muhamad (Jurnal Iqtisad, 2002)
Assumption that accounting is a value free science and practice has been critized since 1970s. There is a very basic question that accounting is value free or not. Some fundamental concepts are now re-questioned, i.e: interest position, basic assumption or concept and its impact on practise, and also methodology. This paper discuss about Islamic perspective on accounting and practise, or known as shariah accounting. Shariah accounting based on the main Islamic source Al Qur’an and Hadist, both on its paradigm and practise. It has not only a social orientation but also a responsibility orientation. Shariah accounting will report social impact of an activity and a humanistic, emancipatoric, transcendental and theological responsibility. In Islamic terminology, shariah accounting is a zakah and amanah oriented.